2008
DOI: 10.1108/02635570810844106
|View full text |Cite
|
Sign up to set email alerts
|

An empirical evaluation of key factors contributing to internet abuse in the workplace

Abstract: Purpose-This study seeks to synthesize theories from communication, psychology and criminology to examine the factors that influence the two most popular topics in industry-internet abuse and addiction at the workplace. Design/methodology/approach-The survey results of 351 responses were analyzed to test the proposed hypotheses and research model using structural equation modeling. Data were collected in Southern Science Park in Taiwan. Findings-It was found that personality factors such as locus of control an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 44 publications
3
43
1
3
Order By: Relevance
“…The results of the statistical analysis, the values of the correlation coefficient r and the p parameter from the regression analysis confirmed some results presented in previous studies (Chen, 2008) namely Internet addiction is strongly correlated to the addiction to several Internet services. Internet-addicted people in Slovenia have similar feeling like being isolated from the real social environment and feeling of loneliness.…”
Section: General Overviewsupporting
confidence: 87%
See 3 more Smart Citations
“…The results of the statistical analysis, the values of the correlation coefficient r and the p parameter from the regression analysis confirmed some results presented in previous studies (Chen, 2008) namely Internet addiction is strongly correlated to the addiction to several Internet services. Internet-addicted people in Slovenia have similar feeling like being isolated from the real social environment and feeling of loneliness.…”
Section: General Overviewsupporting
confidence: 87%
“…In that context they are considered to abuse their duties due to the diagnosed Internet addiction. Deviant use of the Internet in the workplace, which is usually described as personal use of the services provided by an Internet network within the work environment and as an abuse was approached in 2008 by few authors (Chen, 2008). It was considered that the abuse happen when an employee voluntary use Internet services during working hours using company resources outside of his/her customary job/work requirements.…”
Section: Internet Addiction and Internet Abusementioning
confidence: 99%
See 2 more Smart Citations
“…External locus of control was found to be related to personal Internet use (Blanchard and Henle, 2008) suggesting that employees who used the Internet for personal purposes believed that getting caught on the act was purely by chance or bad luck. Similarly, in Chen et al (2008), locus of control has been found to significantly influence employees' Internet use at the workplace. Therefore, we posited that:…”
Section: Locus Of Controlmentioning
confidence: 95%